Study the Utility of S100 Protein and Vimentin as a Marker for Neoplastic Myoepithelial Cells in Salivary Gland Neoplasms - Kanika Munish; Mamta Gupta; Rani Bansal (Archives of Medicine and Health Sciences)
Background and Aim: Complexity of salivary gland tumors (SGTs) is attributed to the presence of myoepithelial component. S100P and vimentin can serve as potential markers in staining the neoplastic myoepithelial cells (NMECs), thus helping in understanding the origin of various SGTs. The study aimed at identifying the NMECs with the help of vimentin and S100 protein and correlating its expression in tumors. Materials and Methods: The study included 32 cases of primary SGTs. Expression of S100P and vimentin was analyzed in NMECs and luminal cells in different tumors. The expression was recorded as positive/negative and weak/strong intensity of staining. Positivity in ductal/acinar (luminal) cells was documented in cases with positive staining. Descriptive data analysis was done. Results: Pleomorphic adenoma (PA) was the most commonly diagnosed tumor, and all cases showed positive expression for vimentin and S100 in NMECs. Vimentin was also positive in adenoid cystic carcinoma (ACC), intraductal papilloma, and PA component of carcinoma ex PA. S100 was positive in NMECs in intraductal papilloma, lymphoepithelial cyst, ACC, secretory carcinoma, and PA component of carcinoma ex PA. Both markers showed negative expression in mucoepidermoid carcinoma and Warthin tumor. Conclusion: Expression of vimentin and S100 in NMECs explains the histogenesis and varied morphological patterns of different SGTs. Immunohistochemical staining can enhance the accuracy and act as a helpful tool in differential diagnosis of SGTs with overlapping morphological features.